Combined frequency domain feedforward and turbo decision feedback equalization for single carrier W-LAN systems - Koppler, Alois; Springer, Andreas; Weigel, Robert (IEEE International Conference on Communications, 2003)
Single carrier transmission with frequency domain equalization (SC/FDE) has been shown to be a promising alternative to orthogonal frequency division multiplexing (OFDM) systems for wireless LANs. In this work we add time domain turbo decision feedback equalization to conventional SC/FDE for block transmission with cyclic prefix. The proposed scheme achieves the potential of ideal decision feedback equalization. Simulation results show a considerable performance increase for highly frequency selective radio channels given in W-LAN environments.
elib2cris::1512001600,koppler2003a